Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T02:15:43+01:00
A) (1024-2⁷)*343 / 2⁷*7⁵
= [2¹° -2⁷)*7³]: 2⁷*7⁵=
= [ 2⁷(2³ -1)*7³] :2⁷*7⁵=
= (2³ -1)*7³ *7⁵ =
= 7*7⁸=
=7⁹ ( 7 do potęgi 9)

b) 1080*6⁴+6⁷ / (6³)²
=(5*6³ *6⁴ +6⁷) : 6⁶ =
= (5* 6⁷ +6⁷ ) : 6⁶=
= 6⁷(5 +1) :6⁶ =
= 6⁷*6 : 6⁶ =
= 6⁸ : 6⁶ =
= 6²=
=36

c) 2¹⁷*x-16⁴*3 = 5*(4⁸*x-3*2¹⁷)
2¹⁷*x - (2⁴)⁴*3 = 5[ (2²)⁸x -3*2¹⁷]
2¹⁷ x =3*2¹⁶ = 5[ 2¹⁶x -3*2¹⁷]
2¹⁶(2x-3) = 5*2¹⁶[ x -3*2] dzielimy przez 2¹⁶
2x-3 = 5(x-6)
2x -3 = 5x-30
2x -5x = -30 +3
-3x = -27 /:(-3)
x = 9


d) 27³*2x-3⁹ = 3¹⁰*x+2*3⁹
(3³)³*2x - 3⁹ = 3⁹(3x +2)
3⁹ *2x - 3⁹ = 3⁹(3x +2)
3⁹(2x-1) = 3⁹(3x +2) / :3⁹ (dzielę przez 3 do potegi 9 )
2x -1 = 3x +2
2x -3x = 2 +1
-x = 3
x = -3